Dispersion of the energy distribution as a function of fission-fragment masses - Montoya, Modesto (1985)
Once again, the width of the total kinetic energy distribution for thermal neutron induced fission of U-235 and Pu-239 was measured as a function of the fragment mass-ratio. Data were obtained by means of the "double energy method" with an experimental lay-out specifically designed to eliminate possible error sources. An appropriate Monte-Carlo procedure was used to correct the raw data for all dispersion effects induced by prompt neutron emission. These "corrected" data clearly demonstrate that most, of the sharp variation in the observed width, σ EK (μ) previously interpreted as having some real physical origin, are in fact generated by the "uncorrected" raw data as such. Similarly treated data, obtained with the Lohengrin mass-spectrometer, are also discussed.